Theoretical analysis of stack gas emission velocity measurement by optical scintillation - 杨阳 董凤忠 倪志波 庞涛 曾宗泳 吴边 张志荣 (Chinese physics B, 2014)
Theoretical analysis for an online measurement of the stack gas flow velocity based on the optical scintillation method with a structure of two parallel optical paths is performed. The causes of optical scintillation in a stack are first introduced. Then, the principle of flow velocity measurement and its mathematical expression based on cross correlation of the optical scintillation are presented. The field test results show that the flow velocity measured by the proposed technique in this article is consistent with the value tested by the Pitot tube. It verifies the effectiveness of this method. Finally, by use of the structure function of logarithmic light intensity fluctuations, the theoretical explanation of optical scintillation spec- tral characteristic in low frequency is given. The analysis of the optical scintillation spectrum provides the basis for the measurement of the stack gas flow velocity and particle concentration simultaneously.